BUDAYA PATRIARKI DALAM TRADISI PERNIKAHAN DI SUMATERA BARAT - Ramadhani, Yerix (Center for Gender and Children Studies, Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) UIN Sultan Thaha Saifuddin Jambi, 2022)
This study explores the role of patriarchy in marriage traditions in West Sumatra and how social transformation affects these dynamics. Although the Minangkabau people are known for their matrilineal system, patriarchal values are still dominant in daily life, especially in marriage. Through a qualitative approach, this study uses in-depth interviews, observations, and documentation to collect data from various related parties, including married couples, traditional leaders, and local cultural experts. The findings suggest that patriarchy plays an important role in determining gender roles in wedding processions, with men often placed as leaders and decision-makers. However, there are signs of change driven by education and urbanization, which is pushing young couples to demand gender equality in marriage. This study also found resistance from the older generation and rural communities who still hold fast to patriarchal values. Thus, this study fills the gap in the literature by providing insight into the experience of couples in navigating patriarchal norms and the implications of social change on marriage traditions in West Sumatra